INVESTIGATION OF ELECTROCHEMICAL-THERMAL COUPLING IN LIFEPO₄ BATTERIES USING A REFERENCE ELECTRODE UNDER FAST-CHARGING CONDITIONS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
The increasing demand for rapid charging of lithium-ion batteries has intensified concerns regarding lithium plating, accelerated degradation, and thermal safety. Conventional battery monitoring systems primarily rely on cell voltage and temperature measurements, which provide limited information about the electrochemical state of individual electrodes. In this study, a three-electrode LiFePO₄ graphite battery incorporating a reference electrode was employed to investigate the relationship between anode potential evolution and thermal behavior during charging. Simultaneous measurements of anode potential, internal temperature, and surface temperature were performed under different charging conditions [1].  The results demonstrate that increasing charging current significantly reduces anode potential while increasing the temperature difference between the battery core and surface. Analysis indicates that changes in anode potential occur prior to significant thermal responses, suggesting that electrochemical signals can serve as early indicators of lithium plating risk and thermal instability.
Keywords: Lithium-ion battery, LiFePO₄, Reference electrode, Fast charging, Anode potential, Thermal behavior, Lithium plating, Battery safety